International Migration from Albania : The Role of Family Networks and Previous Experience - Stampini, Marco (2012)
This paper analyzes the sweeping evolution of Albanian migration since 1990, classifying the phenomenon by destination (toward Greece or other countries) and type (temporary or permanent). Using data from the 2002-3 Living Standards Measurement Study (LSMS) panel data set and the 2001 Housing and Population Census, we show first that the profile of migrants has evolved over time, with the phenomenon spreading to less-educated individuals and to poorer regions of the country. Second, we show that family migration networks and previous personal experience, in conjunction with other individual and household characteristics, are the primary determinants of the decision to migrate. The role of migration networks and personal previous experience varies by type and destination of international migration.